Chiral imines prepared from 1-(2-aminoalkyl)aziridines as novel chiral shifts reagents for efficient recognition of acids. Issue 13 (29th March 2018) - Pieczonka, Adam M.; Leśniak, Stanisław; Rachwalski, Michał
Abstract: Optically pure, chiral imines synthesized from the corresponding aldehydes and 1-(2-aminoalkyl)aziridines in good chemical yields, have been assessed as an NMR chiral shift reagents for effective discrimination of the signals of some acids (mandelic acid and its derivatives and N -protected amino acid). The title compounds have proven to be very useful for the determination of enantiomeric purity and absolute configuration of the aforementioned acid derivatives. Graphical abstract: